A surface plasmon resonance immunoassay for the rapid analysis of methamphetamine in forensic oral fluid. Issue 9 (2nd August 2019) - Wang, Jiye; Yao, Weixuan; Meng, Fanwei; Wang, Pengjuan; Wu, Yuanzhao; Wang, Binjie
Abstract: Background: Current chromatographic methods applied for the forensic analysis of methamphetamine are costly, time‐consuming, and require complicated pretreatment procedures. Thus, the rapid detection of methamphetamine is a critical and unmet need. In this study, a surface plasmon resonance (SPR) system based on indirect inhibitive immunoassay was designed for the analysis of methamphetamine in forensic oral fluid samples. Methods: For the inhibition immunoassay, the diluted oral fluid was mixed with methamphetamine antibody and then injected into the SPR sensor chip. The biosensor chip was constructed by covalently immobilizing of methamphetamine‐bovine serum albumin conjugate onto a carboxymethyl dextran surface at an optimized pH. The concentration of antibody was also optimized. Results: The SPR biosensor showed good sensitivity with a limit of detection of 0.44 ng/mL and was comparable or lower than the pre‐existing methods. The method was finally tested using oral fluid samples from 20 suspected drug abusers in forensic cases, and it provided an acceptable recovery of 113.2%, indicating good anti‐interference capability of the SPR sensor. Conclusion: The SPR biosensor was rapid, reproducible, and had a great potential approach for the forensic detection of methamphetamine.